STAGES OF DEVELOPMENT OF MECHANISMS TO ENSURE COMPETITIVENESS OF THE ENTERPRISE (Marketing Journal, 2025)
This article examines the issues of production concentration and economies of scale, which act as another factor in the growth of enterprise competitiveness. But in order for this opportunity to be realized in practice, management companies must increase i nvestments in innovative development, rearrange labor resources, etc.
Keywords: concentration of production; competition; competitiveness of enterprises; investment; innovative development